The use of absorbable skin stapler in mastectomy does not increase the rate of surgical site infection - Lee, Jin; Lee, Jeong Eon; Ryu, Jai Min; Kim, Seok Won; Nam, Seok Jin; Yu, Jong Han (Annals of surgical treatment and research, 2023)
The use of absorbable skin staplers (ASS) for skin closure has been increasing due to their convenience and time-saving effect. In this study, we evaluated the effectiveness of ASS in reducing skin closure time and its safety regarding surgical site infection (SSI), comparing it to conventional hand sewing (HS) in patients who underwent mastectomy. A single-center, retrospective study was conducted. The electronic medical records of patients who underwent mastectomy between July 2015 and June 2020 in Samsung Medical Center were reviewed. The data included previously known risk factors for SSI. We compared the time expended on skin closure and the occurrence rate of SSI between the ASS group and the HS group. We included 4,311 patients in the analysis. Among them, 520 patients were treated with ASS and 3,791 patients with HS. The average time for skin closure was 16.2 ± 10.1 minutes in the ASS group and 36.5 ± 29.0 minutes in the HS group (P < 0.001). The SSI rate was 0.38% (2 of 520) in the ASS group and 0.36% (14 of 3,791) in the HS group (P > 0.999). The use of ASS in mastectomy reduced the time for skin closure significantly but did not increase the SSI. Therefore, it can be an effective and safe choice to use ASS instead of HS for skin closure in mastectomy.